PERAN BALAI KONSERVASI SUMBER DAYA ALAM JAKARTA DALAM PENCEGAHAN DAN PEMBERANTASAN PERDAGANGAN ILEGAL SATWA LIAR - Diah Retnowati; Azis Nur Arifin; Ramlin Ahmad (Universitas Kapuas, 2026)
llegal wildlife trade has become a serious environmental crime that threatens biodiversity conservation and ecological sustainability, particularly in urban areas such as Jakarta where trade networks are highly developed. This article aims to analyze the role of the Jakarta Natural Resources Conservation Agency (Balai Konservasi Sumber Daya Alam Jakarta) in preventing and combating illegal wildlife trade and to assess the effectiveness of conservation law enforcement in an urban context. This research employs a normative legal research method using statutory and conceptual approaches, supported by secondary data derived from legislation, official government reports, and relevant scientific literature. The findings indicate that although BKSDA Jakarta has implemented supervisory and enforcement measures in accordance with Law Number 5 of 1990, its effectiveness remains constrained by limited human resources, weak inter-agency coordination, and inadequate capacity to address digital-based wildlife trade. In addition, the increasing use of online platforms for wildlife trafficking presents new challenges that are not fully accommodated by existing legal instruments. This study concludes that strengthening institutional capacity, improving cross-sectoral coordination, and adapting law enforcement strategies to technological developments are essential to enhance the effectiveness of wildlife protection and conservation law enforcement in urban areas.